2017
DOI: 10.1016/j.aott.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric all-terrain vehicle (ATV) injuries: An epidemic of cost and grief

Abstract: ObjectiveEvaluate cost of care of all-terrain vehicle (ATV) related injuries sustained by riders 16 years and younger in Pennsylvania.MethodsPopulation-based retrospective cohort design reviewing costs of care of 78 patients (≤16 years), admitted (01/01/2007–12/31/2009) to our institution for injuries sustained during an ATV accident.ResultsCost of care varied from $322 to $310,435. Mean and median costs for all patients were $25,760 and $8,066, respectively. Average costs increased with increasing age. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…The ATV’s design is such that significant co-ordination, strength, judgement and experience are required to achieve safe operation 11. The crash mechanisms characterising ATV events primarily include falls, rollovers and collisions with rollovers crushing the user under the vehicle causing asphyxiation 12.…”
Section: Introductionmentioning
confidence: 99%
“…The ATV’s design is such that significant co-ordination, strength, judgement and experience are required to achieve safe operation 11. The crash mechanisms characterising ATV events primarily include falls, rollovers and collisions with rollovers crushing the user under the vehicle causing asphyxiation 12.…”
Section: Introductionmentioning
confidence: 99%
“…Historical studies such as Percy and Duffy 18 reporting ATV related injuries and Warda and colleagues 1 reporting safety behaviors have called for preventive and safety measures such as consistent use of safety gear, mandatory rider training, as well as consumer and dealer education. Congruently, recent literature also concluded that safety precautions can reduce injury related costs 5 and recommended preventative guidelines 6 or initiatives 10 to reduce ATV related injuries. ATV dealers and track owners may be open to displaying ATV safety information similarly to agribusinesses.…”
Section: Discussionmentioning
confidence: 99%
“…Use of ATVs has been associated with significant injury, mortality, and healthcare cost. 5 Reported ATV related injuries include: bone fractures at or below the cervical spine, specifically femur and tibia 6 , upper extremities, thoracic, peripheral nerve, and soft tissue injuries 4 and traumatic brain injuries. 4 , 7 A recent national review of ATV fatalities reported a rate of .32 per 100,000 8 ; while Garay and colleagues 6 observed a 1.5% mortality rate among all pediatric ATV injuries in Pennsylvania.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cost analysis data reported by Strohecker et al suggest that the use of helmets, advocated by the AAP, only slightly shortened hospital length of stay. 6 A large number of children fail to follow safety precautions when operating ATVs. 7…”
Section: Introductionmentioning
confidence: 99%